Salicylic acid is involved in the Nb-mediated defense responses to Potato virus X in Solanum tuberosum - Sanchez, Gerardo; Gerhardt, Nadia; Siciliano, Florencia; Vojnov, Adrián; Malcuit, Isabelle; Marano, María Rosa (2019)
To evaluate the role of salicylic acid (SA) in Nb-mediated hypersensitive resistance to Potato virus X (PVX) avirulent strain ROTH1 in Solanum tuberosum, we have constructed SA-deficient transgenic potato plant lines by overexpressing the bacterial enzyme salicylate hydroxylase (NahG), which degrades SA. Evaluation of these transgenic lines revealed hydrogen peroxide accumulation and spontaneous lesion formation in an age- and light-dependent manner. In concordance, NahG potato plants were more sensitive to treatment with methyl viologen, a reactive oxygen species--generating compound. In addition, when challenged with PVX ROTH1, NahG transgenic lines showed a decreased disease-resistance response to infection and were unable to induce systemic acquired resistance. However, the avirulent viral effector, the PVX 25-kDa protein, does induce expression of the pathogenesis-related gene PR-1a in NahG potato plants. Taken together, our data indicate that SA is involved in local and systemic defense responses mediated by the Nb gene in Solanum tuberosum. This is the first report to show that basal levels of SA correlate with hypersensitive resistance to PVX.